Alguém me ajuda nessa é expressão numéricas
Anexos:
![](https://pt-static.z-dn.net/files/d1e/1d311bae09566e2c34310844f9a66662.jpg)
Soluções para a tarefa
Respondido por
0
(-27): (-3)-(-4).(-3)+(+3).(+1)
(-27):(-3)+(4).(-3)+(3).(1)
9+(-12)+(3)
-3+3
=0
(-27):(-3)+(4).(-3)+(3).(1)
9+(-12)+(3)
-3+3
=0
Respondido por
1
(-27)÷(-3)-(-4)×(-3)+(+3)×(+1)=
+9-12+3=
-3+3=
0
+9-12+3=
-3+3=
0
Perguntas interessantes
Português,
11 meses atrás
História,
11 meses atrás
Matemática,
11 meses atrás
Português,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás